(untitled) (Al-Academy, 2024)
The study aimed to identify the contemporary aesthetic in art and fractal geometry from an artistic perspective, the historical development of ceramics, contemporary ceramics, methods of forming and processing it, and production of ceramic inspired by fractals. To answer the study question: is it possible to benefit from fractal geometry aesthetics as an input for creating contemporary ceramics? The study assumed that fractal geometry aesthetics could be useful in the production of contemporary ceramics. To verify the validity of the hypothesis, the descriptive and analytical approach was used in the theoretical part, and the applied approach in the practical part. Ceramics that were distinguished by their contemporary nature were produced by relying on fractal geometry aesthetics. The results confirmed that mathematics and the branches of natural engineering are of the most important entrances through which the artist can build his designs, and that studying the characteristics of fractal geometry develops artistic expertise and provides various plastic solutions. The study recommended conducting more studies on fractal geometry in various artistic fields. And expanding fractal geometry types studies, as well as studies linking the basic and natural sciences and the arts.